ANALISIS PENERAPAN PASAL 245 UU NO. 37 TAHUN 2004 TENTANG KEPAILITAN DAN PKPU DALAM (STUDI KASUS PUTUSAN NO:03/PDT.SUS-PKPU/2016/PN.NIAGA.JKT.PST.) - Henry Prawira; Christine S. T. Kansil (Jurnal Hukum Adigama, 2019)
Bankruptcy has become a common problem in today's business world, under the Bankruptcy and Suspension of Payment Act, in addition to bankruptcy, one can do so through Suspension of Payment. Suspension of Payment is a method of debt-receivable dispute resolution which is supervised by a supervisory and administering judge, whose final legal product is peace or insolvency. Not all Debtors have good intentions, sometimes payments are made after Suspension of Payment's application is registered. According to the Article 245 of Law Number 37 of 2004 on Bankruptcy and Suspension of Payment, all payments made before the Suspension of Payment are not permitted, after the Suspension of Payment application has been applied for and has been registered at the commercial court in the district court. However there is a dualism of understanding of the prohibition, some claim that the payment is permissible, and some claim that the payment is not permitted. Many Debtors use these payments to abort the formal requirements of Suspension of Payment, which is not in accordance with the legal objectives of justice for all parties, because the usual payment is payment to only a portion of creditors, who have smaller debts, which makes other creditors not get legal certainty, and the consequence of that is that PKPU's application must be rejected. The purpose of this study is to find out how to apply Article 245 of Act No. 34 of 2004 as it should, so that it can be adjusted to the purpose of law, namely justice.